Associations between body mass index and physical fitness indicators among Chinese university students: a multicenter cross-sectional study - Hanfeng Wu; Peiyi Lin; Guanghao Zeng; Feiyue Chen (BMC Sports Science, Medicine and Rehabilitation)
Abstract Background Increasing body mass index (BMI) has many negative effects on the physical and mental health of university students and has become a common public health problem in all countries. However, there are few studies on the association between BMI and physical fitness indicators among Chinese university students in developing countries, and the findings are inconsistent. The present study aims to analyze the association between BMI and physical fitness indicators among Chinese university students, to assist in university students’ health development and intervention. Methods In this study, we conducted a cross-sectional assessment of BMI of 29,371 university students and a cross-sectional assessment of physical fitness indicators of vital capacity, sit and reach, pull-up(boys), sit-up(girls), standing long jump, 50 m dash, 1000 m run(boys ), 800 m run(girls). One-way analysis of variance (ANOVA), Pearson’s correlation analysis, and nonlinear regression modeling were used to analyze the associations that existed between BMI and various physical fitness indicators. Results The percentages of Chinese university students in emaciated, normal, overweight, and obese were 17.8%, 65.3%, 14.9%, and 2.0%, respectively. Comparing between different BMI groups (emaciated, normal, overweight, and obesity), for boys, the effect values ranged from 1.0 to 2.0% for the items of vital capacity, sit and reach, pull-up/situp, standing long jump, 50 m dash, and 1000/800 m-run. For run events, the range of effect sizes ranged from 0.2 to 0.9; the range of effect sizes for girls also ranged from 0.2 to 0.9. Conclusions The physical fitness level of emaciated and obese Chinese university students is generally lower than that of normal-weight students, and the relationship between BMI and physical fitness indicators shows a “U-shape” or “inverted U-shape” curve. The effect of BMI on physical fitness is more significant in boys than in university girls. In the future, targeted physical exercise and health education should be provided to emaciated and obese university students to maintain a reasonable body weight and promote the healthy development of physical fitness.